Báo cáo Tổng hợp ý kiến của các vị đại biểu Quốc hội về dự kiến Kế hoạch kiểm toán năm 2024 - Tổng Thư ký Quốc hội (2023)
Toàn văn Báo cáo Tổng hợp ý kiến của các vị đại biểu Quốc hội về dự kiến Kế hoạch kiểm toán năm 2024.